Temperature-responsive dielectric characteristics of MXene–NiO nanocomposite - Demirelli, Kadir; Çiçek, Rabia; Erol, İbrahim; Arslan, İbrahim; Mansour, Shehab A.; Yakuphanoğlu, Fahrettin (Elsevier B.V., 2026)
In the synthesis of two-dimensional Ti3C2Tx MXene derived from the main Ti3AlC2 phase, hydrofluoric acid (HF) was used as an etchant. The NiO was synthesized from Ni(NO3)2·6H2O by the hydrothermal method at 180 °C. To ensure good homogenization of the two components, both MXene and NiO were held in the hydrothermal rig at 180 °C for 12 h. MXene10 wt%-NiO nanocomposite was confirmed by XRD and SEM-EDX techniques. The AC conductivity of the MXene10 wt%-–NiO nanocomposite increases with frequency, following a universal power law, indicating enhanced charge-carrier mobility at higher filler content. The electrical properties of the MXene10 wt%-–NiO nanocomposite were systematically investigated through DC resistivity as a function of temperature and AC conductivity as a function of both frequency and temperature. The activation energy calculated from the Arrhenius relation increased upon NiO incorporation, suggesting a modification in charge-transport dynamics. Furthermore, the dielectric constant (??) and tan ? were analyzed over a wide frequency and temperature range. The observed frequency-dependent variations in ??, tan ? and AC conductivity (?ac) indicate that the dielectric dispersion is predominantly governed by Maxwell–Wagner type interfacial polarization. © 2026 Elsevier B.V.
Keywords: Dielectric properties; MXene; Nanocomposite; NiO